Adipose tissue-derived stem cells promote pancreatic cancer cell proliferation and invasion - Ji,S.Q. (2013)
To explore the effects of adipose tissue-derived stem cells (ADSCs) on the proliferation and invasion of pancreatic cancer cells in vitroand the possible mechanism involved, ADSCs were cocultured with pancreatic cancer cells, and a cell counting kit (CCK-8) was used to detect the proliferation of pancreatic cancer cells. ELISA was used to determine the concentration of stromal cell-derived factor-1 (SDF-1) in the supernatants. RT-PCR was performed to detect the expression of the chemokine receptor CXCR4 in pancreatic cancer cells and ADSCs. An in vitro invasion assay was used to measure invasion of pancreatic cancer cells. SDF-1 was detected in the supernatants of ADSCs, but not in pancreatic cancer cells. Higher CXCR4 mRNA levels were detected in the pancreatic cancer cell lines compared with ADSCs (109.3±10.7 and 97.6±7.6 vs 18.3±1.7, respectively; P<0.01). In addition, conditioned medium from ADSCs promoted the proliferation and invasion of pancreatic cancer cells, and AMD3100, a CXCR4 antagonist, significantly downregulated these growth-promoting effects. We conclude that ADSCs can promote the proliferation and invasion of pancreatic cancer cells, which may involve the SDF-1/CXCR4 axis.